2011
DOI: 10.1007/s11240-011-9933-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sucrose and plant growth regulators on acetylcholinesterase inhibitory activity of alkaloids accumulated in shoot cultures of Amaryllidaceae

Abstract: The influence of sucrose (30, 60, 90 and 120 g/L), activated charcoal (5 and 10 g/L), and various levels of several plant growth regulators (6-benzyladenine, naphthalene-1-acetic acid, 2,4-dichlorophenoxyacetic acid, and picloram) on organogenesis (bulb and root development) and the accumulation of alkaloid and galanthamine in shoot cultures of three Amaryllidaceae species (Narcissus pseudonarcissus, Galanthus elwesii, and Leucojum aestivum) was investigated in a full-factorial experiment. Alkaloid extracts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
1
28
0
2
Order By: Relevance
“…anthraquinones (hypericin, pseudohypericin), phloroglucine derivate (hyperforin) in Hypericum sp. shoot cultures (Coste et al 2011), flavonoid (rutin) in Morus alba in vitro cultures (Lee et al 2011), terpenoids in Camellia sinensis suspension cultures (Grover et al 2012), and alkaloid (galanthamine) production in in vitro cultures of three Amaryllidaceae species (El Tahchy et al 2011). Studies performed in our laboratory have confirmed the effects of NAA and BA concentrations in L-S medium on free phenolic acids accumulation in in vitro cultures of R. graveolens (Ekiert et al 2009) and its subspecies R. graveolens ssp.…”
Section: Discussionmentioning
confidence: 99%
“…anthraquinones (hypericin, pseudohypericin), phloroglucine derivate (hyperforin) in Hypericum sp. shoot cultures (Coste et al 2011), flavonoid (rutin) in Morus alba in vitro cultures (Lee et al 2011), terpenoids in Camellia sinensis suspension cultures (Grover et al 2012), and alkaloid (galanthamine) production in in vitro cultures of three Amaryllidaceae species (El Tahchy et al 2011). Studies performed in our laboratory have confirmed the effects of NAA and BA concentrations in L-S medium on free phenolic acids accumulation in in vitro cultures of R. graveolens (Ekiert et al 2009) and its subspecies R. graveolens ssp.…”
Section: Discussionmentioning
confidence: 99%
“…The low Amaryllidaceae alkaloid accumulation commonly observed in in vitro cultures of Leucojum aestivum [6,[9][10][11][12][13] was probably due to the fact that the level of the alkaloid biosynthesis is strongly influenced by cellular differentiation [10,[14][15][16]. In particular, enhanced synthesis of galanthamine accompanied development of somatic embryos [17].…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrates that a micropropagation system, not involving the production of embryogenic calli, can also be established for this species. Besides our report, several studies reported the production of L. aestivum tissue cultures [7,26], but none of them involved the assay of antioxidant capacities (see below). All cultures showed high shoot / whole plant and (except L. aestivum) high bulblet regeneration frequencies (Tab.…”
Section: Discussionmentioning
confidence: 91%
“…Several tissue cultures of Amaryllidaceae involve the growth regulators NAA, IAA as auxins and BA as a cytokinin [7,10,27,28]. Auxin/cytokinin combinations involving growth regulators mentioned are potent inducers of embryogenic callus formation and/or mass plant propagation in this family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation